SpinOcchio: Understanding Haptic-Visual Congruency of Skin-Slip in VR with a Dynamic Grip Controller - Kim, Myung Jin; Ryu, Neung; Chang, Wooje; Pahud, Michel; Sinclair, Mike; Bianchi, Andrea (CHI 2022, 2022)
This paper's goal is to understand the haptic-visual congruency perception of skin-slip on the fingertips given visual cues in Virtual Reality (VR). We developed SpinOcchio ('Spin' for the spinning mechanism used, 'Occhio' for the Italian word “eye”), a handheld haptic controller capable of rendering the thickness and slipping of a virtual object pinched between two fingers. This is achieved using a mechanism with spinning and pivoting disks that apply a tangential skin-slip movement to the fingertips. With SpinOcchio, we determined the baseline haptic discrimination threshold for skin-slip, and, using these results, we tested how haptic realism of motion and thickness is perceived with varying visual cues in VR. Surprisingly, the results show that in all cases, visual cues dominate over haptic perception. Based on these results, we suggest applications that leverage skin-slip and grip interaction, contributing further to realistic experiences in VR.